Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given $$\sum\limits_{i=0}^\infty a_i z^i=A(z)$$ and $$\sum\limits_{i=1}^\infty b_i z^i=B(z)$$ and $$\sum\limits_{i=0}^\infty c_i z^i=C(z)$$ Find $\sum\limits_{i=1}^\infty\sum\limits_{j=0}^\infty a_j \sum\limits_{k=1}^\infty b_kc_{k+j-i} z^i$ in terms of the generating functions $A(z),B(z),C(z)$.

share|improve this question

1 Answer 1

up vote 1 down vote accepted

Since $i=(j)+(k)-(j+k-i)$, the triple sum is $$\sum\limits_{\alpha,\beta,\gamma}a_\alpha b_\beta c_\gamma z^{\alpha+\beta-\gamma}=A(z)B(z)C(1/z).$$

share|improve this answer
Thank you for your help. Please see this also $\sum\limits_{i=0}^\infty a_i z^i=A(z)$ and $\sum\limits_{j=1}^\infty b_j z^j=B(z)$ and $\sum\limits_{k=0}^\infty c_k z^{-k}=C(1/z)$ Then $\sum\limits_{i=0}^\infty\sum\limits_{j=1}^\infty\sum\limits_{k=1}^\infty a_ib_jc_{i+j-k} z^k=$? –  Litun Feb 20 '13 at 6:40
What are you asking me to do? –  Did Feb 20 '13 at 6:53
Whether this expression is same as the previous one $A(z)B(z)C(1/z)$ –  Litun Feb 20 '13 at 8:13
As $A(z)B(z)=\sum\limits_{i=0}^{\infty}\sum\limits_{j=0}^{i}a_jb_{i-j}$ then what is the expression for $A(z)B(z)C(1/z)$ –  Litun Feb 20 '13 at 8:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.